Factor affecting the Malaysian palm oil export to India - Ahmad, Mohammad Yusof; Kai, Kelly Seng Wong (HH Publisher, 2024)
The huge size of the population and increasing living standards from its growing economy do not give any other choice for India to satisfy the huge demand for edible oils unless importing them from different countries. Currently, India stands as the largest vegetable oils importer in the world, and palm oil from Malaysia is one of its preferences. However, there is a mixed scenery of demand trend shown by India and surprisingly it seems to be significantly changed every five to seven years. Hence, this study is a discovery to reveal the factors that triggered the volatility in India’s demand for Malaysian palm oil. This is important since India is the largest importer of Malaysian palm oil and the switch in India's demand for Malaysian palm oil will affect the Malaysian economy. Thus, the outcome from the ARDL analysis of the study gives its findings by summarizing that the Indian market is highly susceptible to price changes in the long and short run, while it is more responsive towards income in the long run. Consequently, this study suggested the policymaker come out with an effective pricing strategy that applies to the current Indian economic situation at the same time introduce an efficient monetary policy to minimize the risk of currency instability on the export demand.